"Duch demokratycznego kapitalizmu" Michaela Novaka Jego analiza i ocena w kontekście etyki chrześcijańskiej - Świątkowski, Waldemar (Annales. Etyka w Życiu Gospodarczym, 2016)
The paper refers to Michael Novak’s book The Spirit of Democratic Capitalism. In his book Novak advances, among others, the thesis that in the light of the encyclical Laborem Exercens, published by John Paul II (1981), one can speak about some converging elements of Catholic and liberal social thought, e.g.: the creativity of modern labour, which would reflect, however, in the two doctrines the theological symbols of the Creator and His creation. But this paper cools down the enthusiasm of Novak and in six analysed aspects seeks to show that, despite some convergence in the phraseology between “the spirit of democratic capitalism” and “the spirit of Christian ethics”, there extends between them an essential abyss, which is the result of basing each “spirit” on different models of ethics.